Apparent Epigenetic Meiotic Double-Strand-Break Disparity in Saccharomyces cerevisiae: A Meta-Analysis. Issue 1 (1st September 2016) - Stahl, Franklin W; Rehan, Maryam Binti Mohamed; Foss, Henriette M; Borts, Rhona H
Abstract: Previously published, and some unpublished, tetrad data from budding yeast ( Saccharomyces cerevisiae ) are analyzed for disparity in gene conversion, in which one allele is more often favored than the other (conversion disparity). One such disparity, characteristic of a bias in the frequencies of meiotic double-strand DNA breaks at the hotspot near the His4 locus, is found in diploids that undergo meiosis soon after their formation, but not in diploids that have been cloned and frozen. Altered meiotic DNA breakability associated with altered metabolism-related chromatin states has been previously reported. However, the above observations imply that such differing parental chromatin states can persist through at least one chromosome replication, and probably more, in a common environment. This conclusion may have implications for interpreting changes in allele frequencies in populations.